Factors Study Influencing on Numerical Simulation of Aircraft Windshield against Bird Strike - F.S. Wang; Z.F. Yue; W.Z. Yan (Shock and Vibration)
The combined model of UniGraphics(UG) and ANSYS-LS-DYNA software and finite element (FE) model of aircraft windshield and windshield structure for bird strike were built. The windshield structure is composed of windshield, framework, arc-frame and gasket. The factors influencing on dynamic response for bird strike were analyzed such as bird velocity, mesh density of windshield, mesh density of bird, boundary condition, material model of windshield, analytic methods and components of windshield structure. The results showed that these factors must be taken into account when FE analysis method is applied to aircraft anti-bird design.